Effectiveness of stationary cycling with electromyographic biofeedback on neuromuscular control and function in individuals with knee osteoarthritis: a feasibility study - Chia-Ming Chang; Huynh Chung; Horng-Chaung Hsu; Li-Tzu Chen; Ruei-Yi Lin; Hsiu-Chen Lin (BMC Musculoskeletal Disorders)
Abstract Background To evaluate the effects of stationary cycling with electromyographic (EMG) biofeedback on neuromuscular control and function in individuals with knee osteoarthritis (OA). Methods Fourteen knee OA patients were randomized into two groups: cycling with EMG biofeedback of the vastus medialis (EBF group) and cycling without biofeedback (Cycling group). Both groups underwent a six-week cycling program, 30 min per session, twice a week. Outcomes were measured at baseline and post-training. Knee pain and function were assessed using the Visual Analog Scale and the Knee Injury and Osteoarthritis Outcome Score (KOOS). Quadriceps strength and endurance were evaluated with an isokinetic machine, and muscle activation was recorded using a wireless EMG system. A two-way mixed-model analysis of variance (ANOVA) was used to assess the differences between sides and groups. For outcomes that were not normally distributed, the non-parametric Mann-Whitney U test was performed. Results Both groups showed improvements in knee pain and function, with no significant differences between groups. Muscle strength remained largely unchanged, but the endurance was improved on the contralateral side (p = 0.038, η2 = 0.312). Larger muscle activations were observed at various time points during the 30-minute cycling test in the EBF group with significant increases in muscle recruitment in the vastus medialis (p = < 0.001 ~ 0.042, η2 = 0.482 ~ 0.996), rectus femoris (p = 0.003 ~ 0.040, η2 = 0.493 ~ 0.859) and vastus lateralis (p = 0.002 ~ 0.036, η2 = 0.534 ~ 0.875). Conclusions A six-week cycling program can alleviate pain and enhance knee function. EMG biofeedback of the vastus medialis significantly changed the neuromuscular control in the rectus femoris and vastus lateralis during cycling. Therefore, this study demonstrated that stationary cycling combined with electromyographic biofeedback training can enhance neuromuscular control of the quadriceps and potentially improve functional performance in patients with OA. Trial registration ClinicalTrials.gov identifier, NCT03484910 (registered at March 31st, 2018).